Decellularized Extracellular Matrix for Cell Biology. Issue 12 (8th December 2021) - Hoshiba, Takashi
Abstract: The extracellular matrix (ECM) is an architecture that supports the cells in our bodies and regulates various cell functions. The ECM is composed of many proteins and carbohydrates, and these molecules activate various intracellular signaling pathways orchestrated to decide cell fates. Therefore, it is not enough to study the role of single ECM molecules to understand the roles of the ECM in the regulation of cell functions; it is necessary to understand how the ECM, as an assembly of various molecules, regulates cell functions as a whole. For this purpose, in vitro ECM models mimicking native ECM are required. Here, a decellularization technique is presented to reconstitute native ECM in vitro. In this article, methods for preparing decellularized ECM (dECM) are described for use in tumor and stem cell biology. Additionally, a method for confirmation of decellularization and a dECM modification method are described. These dECM types will be useful for comprehensive studies of ECM roles. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of in vitro extracellular matrix (ECM) models mimicking native ECM in different malignant tumor tissues Basic Protocol 2 : Preparation of in vitro ECM models mimicking native ECM surrounding myoblasts differentiating into myotubes at each myogenic stage Support Protocol 1 : Confirmation of myogenic stages by myogenic stages by myogenic gene expression analysis Basic Protocol 3 : Confirmation of cell removal Basic Protocol 4 : Reduction of chondroitin sulfate chains in cultured cell–derived decellularized ECM Support Protocol 2 : Quantification of chondroitin sulfate chain amounts in the decellularized ECM